Best practices of effective classroom management strategies supported by digital ICT in higher education - Mahmoud, Enaz; Bawaneh, Ali Khaled (Institute of Advanced Engineering and Science, 2025)
In the field of higher education, incorporating digital information and communication technology (ICT) into classroom management has gained significant attention due to its potential benefits in enhancing students’ engagement and learning. One of the significant challenges in higher education is managing students learning in the classroom effectively. Higher education students cannot gain effectively the targeted learning outcomes by using regular classroom management in teaching higher education subjects away from digital ICT. The purpose of this study is to explore the advantages of using digital ICT tools into classroom management in higher education and to discuss the challenges and considerations that are involved in this process. This study uses the descriptive research methodology that does not include or present students during preparing of the suggested framework, because it suggests a well-designed cohesive framework of preparing steps, best digital ICT software programs, and the most suitable practical techniques for ICT effective classroom management. It describes the best practices of using 10 professional ICT digital software tools for effective integration and provides examples of practical techniques at the higher education level using suggested ways of successful implementation. It finds that using these software programs can lead students to engage in classroom activities actively, increase their academic achievement, and maximize their technology communication skills. It recommends that providing instructors with enough ICT digital professional development programs and the availability of most updated digital infrastructure are crucial factors for effective classroom management.